TEXTUAL REDUCTIONISM: FROM ENGINEERING RESEARCH ARTICLES (RAs) TO THEIR SUBSEQUENT POSTERS - EL-Sakran, Tharwat M. (Indonesian Journal of Learning and Instruction, 2019)
Converting a Research Article (RA) into a poster is a complex, recursive reading-writing activity that can impose an overwhelming cognitive load on designers. This study contributes to a growing body of research which emphasizes the importance of designing clear academic posters. It proposes practical guidelines for academic poster design and contents. A total of 20 published RAs with their subsequent posters from the engineering field were analyzed to see what elements of the RAs were modified, changed or totally removed. Several software packages were used for this investigation. A correlation was found between the length of the RA and the amount of RA contents retained in the poster. Analyses also show that function words, the literature review section and the list of references were the main victims of heavy reductionism. However, comparisons of RAs and their related posters revealed that visuals were the least sacrificed textual items in the reduction process. It is proposed that poster contents may reflect the original RA structure with more emphasis allotted to new information in the research. Such a practice will help reduce the limitations that the poster space may impose on the contents, allow the poster presenter more freedom to use a bigger font size, and most importantly; interact and engage actively with the interested audience. The research concludes with limitations and recommendations for further research.